Paul and the Faithfulness of God: Christian Origins and the Question of God, Vol 4 - Wright, N. T. (SPCK, 2013)
?Tom Wright's long-awaited full-length study of St Paul will not in any way disappoint the high expectations that surround it. From the very first sentence, it holds the attention, arguing a strong, persuasive, coherent and fresh case, supported by immense scholarship and comprehensive theological intelligence. It is a worthy successor to his earlier magisterial studies of the themes of the Kingdom and the Resurrection: lively, passionate and deeply constructive, laying out very plainly the ways in which the faith of the New Testament is focused on God's purpose to re-create, through the fact